Awareness of Antithyroid Drug-Induced Agranulocytosis in Patients with Thyrotoxicosis - Abunamous, Nasser; Takaleh, Akram; Abdelsalhen, Mohamed; Alqedra, Mohamed; Abbara, Amena; Almazrouei, Raya; Agha, Adnan (Journal of Diabetes and Endocrine Practice, 2025)
Objective Anti-thyroid drugs (ATDS)-induced agranulocytosis is a serious side effect that can be treated by early management if the patient has been educated to promptly self-identify agranulocytosis based on its presenting features. We aimed to assess the knowledge of patients taking carbimazole for hyperthyroidism regarding suspected agranulocytosis.Methods This questionnaire-based cross-sectional study with prospective follow-up analyzed adult patients with hyperthyroidism who visited an endocrine clinic, in a tertiary hospital in the UAE, between January 2023 and March 2024. They were asked about their knowledge about the symptoms of agranulocytosis and the immediate steps required upon symptom observation. They were then given bilingual agranulocytosis information cards and educated either face-to-face or telephonically. Their knowledge and awareness were re-evaluated 3-6 months later. Chi-squared tests were used to assess the differences before and after patient education.Results The initial and follow-up surveys were answered by 68 patients (mean age: 43.7 ± 17.1 years). The cohort included 48 (70.6%) females and 58 (85.3%) Emiratis. Hypothyroidism was due to Graves' disease in 64 (94.1%) patients and toxic multinodular goiter in 4 (5.9%) patients. There were 41 (60.3%) participants who responded that they had received adequate information on ATD-related agranulocytosis upon treatment initiation, which improved to 67 (98.5%) following patient education. Similarly, their self-reported confidence in identifying ATD-related side effects significantly improved (50% [34/68] vs. 100% [68/68]; p < 0.00001) after receiving education.Conclusion Patient education and information cards on ATD-induced agranulocytosis improve patient awareness regarding symptom identification and the next steps required for suspected agranulocytosis.
Keywords: antithyroid drugs; drug-induced agranulocytosis; carbimazole; hyperthyroidism; thyrotoxicosis